Analysis of The Elements of Logistics Customer Service In Freight Forwarding - Purwoko, Harry; Thamrin, HM; Yuliyanto, Agus; Sembiring, Honny Akira (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2022)
Logistics is as service industry that relies heavily on people to execute operations in order to provide a better perception to customers through customer service. In stiff competition, customer service will make a big difference between competitors. A qualitative study using in-depth interview analyse the effectiveness of implementing three elements of logistics customer service, i.e., pre-transactions, in transactions and post-transactions, particularly in the international freight forwarding activities to understand the three elements of customer service transactions. The result shows a strong relationship and impact between the elements, although most of the topics in these elements are not relevant to freight forwarding industry.